Co-delivery of PLGA nanoparticles loaded with rSAG1 antigen and TLR ligands: An efficient vaccine against chronic toxoplasmosis. (January 2022) - Allahyari, Mojgan; Golkar, Majid; Fard-Esfahani, Pezhman; Dimier-Poisson, Isabelle; Mévélec, Marie-Noëlle
Abstract: Although vaccination is a promising approach for the control of toxoplasmosis, there is currently no commercially available human vaccine. Adjuvants such as delivery vehicles and immunomodulators are critical components of vaccine formulations. In this study, Poly (D, l -lactide-co-glycolide) (PLGA) nanoparticles were applied to serve as delivery system for both surface antigen-1 (SAG1), a candidate vaccine against toxoplasmosis and two TLR ligands, monophosphoryl lipid A (MPL) and imiquimod (IMQ), respectively. Compared to rSAG1 alone, CBA/J mice immunized with rSAG1-PLGA produced higher anti-SAG1 IgG antibodies titers. This response was increased by the co-administration of IMQ-PLGA ( p < 0.01). Compared to IMQ-PLGA co-administration, MPL-PLGA co-administration further increased the humoral response ( p < 0.01) and potentiated the Th1 humoral response. Compared to rSAG1 alone, rSAG1-PLGA, or rSAG1-PLGA mixed with IMQ-PLGA or MPL-PLGA similarly enhanced the cellular response characterized by the production of IFN-γ, IL-2, TNF-α and low levels of IL-5, indicating a Th1-biased immunity. The induced immune responses, led to significant brain cyst reductions ( p < 0.01) after oral challenge with T. gondii cysts in mice immunized with either rSAG1-PLGA, rSAG1-PLGA + IMQ-PLGA, rSAG1-PLGA + MPL-PLGA formulations. Taken together the results indicated that PLGA nanoparticles could serve as a platform for dual-delivery of antigens and immunomodulators to provide efficacious vaccines against toxoplasmosis. Graphical abstract: Image 1 Highlights: PLGA nanoparticles for delivery of antigens and immunomodulators (MPL or IMQ). Surface antigen-1 (SAG1) is a well known candidate vaccine against toxoplasmosis. Compared to SAG1 alone, PLGA clearly potentiated both humoral and cellular immunity. Compared to PLGA, MPL-PLGA potentiated the Th1 humoral response. IMQ-PLGA potentiated the humoral response but not the Th1 humoral response.